South Africa: Agritel Agricultural Information Services - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Agritel Agricultural Information Services makes available the daily market prices and volumes of all products sold on the South African fresh produce markets on the Internet and by e-mail.